Structure, topology, and dynamics of membrane-inserted polypeptides and lipids by solid-state NMR spectroscopy: investigations of the transmembrane domains of the DQ beta-1 subunit of the MHC II receptor and of the COP I protein p24 - Salnikov, Evgeniy S.; Aisenbrey, Christopher; Pokrandt, Bianca; Brügger, Britta; Bechinger, Burkhard (Frontiers in molecular biosciences, 2019)
MHC class II receptors carry important function in adaptive immunity and their malfunctioning is associated with diabetes type I, chronic inflammatory diseases and other autoimmune diseases. The protein assembles from the DQ alpha-1 and DQ beta-1 subunits where the transmembrane domains of these type I membrane proteins have been shown to be involved in homo- and heterodimer formation. Furthermore, the DQ alpha 1 chain carries a sequence motif that has been first identified in the context of p24, a protein involved in the formation of COPI vesicles of the intracellular transport machinery, to specifically interact with sphingomyelin-C18 (SM-C18). Here we investigated the membrane interactions and dynamics of DQ beta-1 in liquid crystalline POPC phospholipid bilayers by oriented 15N solid-state NMR spectroscopy. The 15N resonances are indicative of a helical tilt angle of the membrane anchor sequence around 20o. Two populations can be distinguished by their differential dynamics probably corresponding the DQ beta-1 mono- and homodimer. Whereas this equilibrium is hardly affected by the addition of 5 mole% SM-C18 a single population is visible in DMPC lipid bilayers suggesting that the lipid saturation is an important parameter. Furthermore, the DQ alpha-1, DQ beta-1 and p24 transmembrane helical domains were reconstituted into POPC or POPC/SM-C18 lipid bilayers where the fatty acyl chain of either the phosphatidylcholine or of the sphingolipid have been deuterated. Interestingly in the presence of both sphingolipid and polypeptide a strong decrease in the innermost membrane order of the POPC palmitoyl chain is observed, an effect that is strongest for DQ beta-1. In contrast, for the first time the polypeptide interactions were monitored by deuteration of the stearoyl chain of SM-C18. The resulting 2H solid-state NMR spectra show an increase in order for p24 and DQ alpha-1 which both carry the SM recognition motif. Thereby the data are suggestive that SM-C18 together with the transmembrane domains form structures imposing positive curvature strain on the surrounding POPC lipids. This effect is attenuated when SM-C18 is recognized by the protein.